Structured illumination microscopy for super-resolution and optical sectioning - Dan, Dan; Yao, Baoli; Lei, Ming (Chinese science bulletin, 2014)
Optical microscopy plays an essential role in biological studies due to its capability and compatibility of non-contact, minimally invasive observation and mea- surement of live specimens. However, the conventional optical microscopy only has a spatial resolution about 200 nm due to the Abbe diffraction limit, and also lacks the ability of three-dimensional imaging. Super-resolution far- field optical microscopy based on special illumination schemes has been dramatically developed over the last decade. Among them, only the structured illumination microscopy （SIM） is of wide-field geometry that enables it easily compatible with the conventional optical microscope. In this article, the principle of SIM was introduced in terms of point spread function （PSF） and optical transform function （OTF） of the optical system. The SIM for super-resolution （SIM-SR） proposed by Gustafsson et al. and the SIM for optical sectioning （SIM-OS） pro- posed by Neil et al. are the most popular ones in the research community of microscopy. They have the same optical configuration, but with different data post- processing algorithms. We mathematically described the basic theories for both of the SIMs, respectively, and pre- sented some numerical simulations to show the effects of super-resolution and optical sectioning. Various approaches to generation of structured illumination patterns were reviewed. As an example, a SIM system based on DMD- modulation and LED-illumination was demonstrated. A lateral resolution of 90 nm was achieved with gold nanoparticles. The optical sectioning capability of the microscope was demonstrated with Golgi-stained mouse brain neurons, and the sectioning strength of 930 nm was obtained.